Omeya: Water, work and infrastructure in Ovamboland from 1915 to 1968 - Vigne, Benjamin (Department of Historical Studies, 2020)
This dissertation seeks to explore the ways in which the multiple layers of infrastructure and archive have been coconstituted in Ovamboland from 1915 to 1968 in an effort to store, circulate and redirect water and its knowledge, which in turn seemed to frequently escape and exceed them. In the existent historiography of Ovamboland, infrastructure has usually been taken as a passive background to policies, designs and intentions of an all-knowing colonizing state. In foregrounding infrastructure as its analytical object, this thesis attempts to challenge such self-images of the state, to complicate the standard political chronology of rule, and to examine the various ways in which technical assemblages were both constituted by and productive of broader social, political and economic configurations. Methodologically, the dissertation is attentive to the spiral and palimpsestic nature of infrastructure – in other words, the ways in which new layers of infrastructure had to necessarily rely on, adopt and adapt to older sociotechnical strata. This awareness also allows the work to interrogate the received binary between the Europeans and the natives, pointing instead at their multiple entanglements and imbrications. The first chapter looks at the early attempt of the South African officials to master the underground borehole and well technology, and shows how in the process of extending their political and economic control over the hydroscape, they were necessarily reliant not only on local labour but also on indigenous knowledge and experience. The emergent borehole and well infrastructure of the region was critically connected to older social, political, A b s t r a c t epistemological and technical forms, and embedded in entrenched configurations of cattle, agriculture and land. The second chapter, as it were, moves closer to the surface in order to analyse the production of dam infrastructure as a form of famine-relief work, and eventually the introduction of the Tribal Trust Fund System. It shows how this dam infrastructure, while drawing from precolonial designs and local knowledge, established and acted out new relations between money, grain and labour. Crucially embedded in the colonial refashioning of ‘tribal' economies, the financial infrastructure of the Tribal Trust Fund System, superimposed on the well and dam infrastructure, was devised to operationalise a particular managerial regime of the flows of labour, grain and cash. The third chapter looks at such forms of water infrastructure where the state took a more centralised and developmental approach. It shows that in the attempts to manage the water infrastructure in a self-described scientific and technical manner, the new infrastructure still necessarily adapted to and adopted earlier knowledge, techniques and practices, while older layers of infrastructure continued to operate beside and within it. This chapter explores how the introduction of major canals and hydroelectric power generation led to a new intense developmentalist approach by the state where attempted to design a total integrated water infrastructure and economy.